رخصة البناء الخاصة بالأراضي الفلاحية (دراسة مقارنة بين التشريعين الجزائري والتونسي) - محمد لمين, سلخ (University of Eloued جامعة الوادي, 2020)
تعتبر رخصة البناء الخاصة بالأراضي الفلاحية، آلية حقيقية من أجل حماية هذا الصنف من العقار، وفي نفس الوقت تعتبر أداة لخلق التوازن بين ضرورة المحافظة على الأرض وضرورة إثمارها واستغلالها بشكل أنجع وأجدى. وذلك عن طريق فرض شروط خاصة بهذه الرخصة، سواء من حيث صفة طالبها أو من خلال مساحة الأرض الفلاحية الدنيا المسموح بالبناء عليها، والمساحة القصوى للمباني والمنشآت المقامة، وكذا شروط أخرى تتعلق بغرض الاستعمال ومواصفات التشييد. الكلمات المفتاحية: رخصة البناء؛ الأراضي الفلاحية؛ حماية؛ قانون عقاري؛ منشآت الاستغلال؛ سكنات؛ قانون جزائري؛ قانون تونسي. The building permit for agricultural land is a real mechanism to protect this type of property, while at the same time it is a tool to create a balance between the need to preserve the land and the need to fruition and use it more efficiently and effectively. By imposing special conditions for this license, whether in terms of the applicant's status or through the minimum agricultural land allowed to be built, the maximum area of buildings and installations established, as well as other conditions related to the purpose of use and construction specifications. ey words: construction license; Agricultural lands; protection; Real estate law; Exploitation facilities; housing; Algerian law; Tunisian law.
مجلد11، عدد1
Keywords: رخصة البناء ; الأراضي الفلاحية ; حماية ; قانون عقاري ; منشآت الاستغلال ; سكنات ; قانون جزائري ; قانون تونسي; Construction permit; agricultural lands; real property law; exploitation facilities; preservation; Algerian legislation; Tunisian legislation.